Lexical homonymy as a problem of linguistic textology (Based on Njegoš’s Epic Stephen the Little) - Marojević Radmilo N. (Serbian Academy of Sciences and Arts, Institute for the Serbian Language, Belgrade, 2021)
The author of this paper explains the interpretation of types of homonyms (homophones and homographs), based on the epic Stephen the Little by the Serbian poet Petar II Petrović Njegoš, dating from the epoch of Romanticism. The analysis includes grammatical homonyms, where homonymy is established by individual word forms created through the motion of nouns and their base forms, and paradigmatic homonyms, where homonymy is established by a whole system of word forms created by semantic formation. The analysis also encompasses material from the epics The Mountain Wreath and The Ray of the Microcosm, and certain poems by Njegoš.